2020
DOI: 10.1126/scitranslmed.aay0289
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A inhibition reduces seizure activity in a mouse model of focal cortical malformations

Abstract: Epilepsy treatments for patients with mechanistic target of rapamycin (mTOR) disorders, such as tuberous sclerosis complex (TSC) or focal cortical dysplasia type II (FCDII), are urgently needed. In these patients, the presence of focal cortical malformations is associated with the occurrence of lifelong epilepsy, leading to severe neurological comorbidities. Here, we show that the expression of the actin cross-linking protein filamin A (FLNA) is increased in resected cortical tissue that is responsible for sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Moreover, postnatal rapamycin treatment reduced soma size regardless of whether treatment began in neonatal or adult ages, suggesting mTORC1 hyperactivation impact neuron size via a dynamic, modifiable process. Dendrite morphology was assessed in the IUE studies targeting Pi3k, Pten, Rheb, and Depdc5, and all revealed dendritic overgrowth involving (for some) increased dendrite thickness and complexity (Chen et al, 2015;Hsieh et al, 2016;Lin et al, 2016;Ribierre et al, 2018;Sokolov et al, 2018;Zhang et al, 2019Zhang et al, , 2020Dawson et al, 2020;Onori et al, 2020;Zhong et al, 2021). Rescue of dendrite morphology by postnatal rapamycin treatment was reported in the Pi3k E545 and Rheb S16H variants, and rapamycin likely has the same effect for the other variants (Zhang et al, 2019;Zhong et al, 2021).…”
Section: Conserved Mtorc1-dependent Phenotypes Across Pi3k-mtor and Gator1 Gene Variantsmentioning
confidence: 99%
“…Moreover, postnatal rapamycin treatment reduced soma size regardless of whether treatment began in neonatal or adult ages, suggesting mTORC1 hyperactivation impact neuron size via a dynamic, modifiable process. Dendrite morphology was assessed in the IUE studies targeting Pi3k, Pten, Rheb, and Depdc5, and all revealed dendritic overgrowth involving (for some) increased dendrite thickness and complexity (Chen et al, 2015;Hsieh et al, 2016;Lin et al, 2016;Ribierre et al, 2018;Sokolov et al, 2018;Zhang et al, 2019Zhang et al, , 2020Dawson et al, 2020;Onori et al, 2020;Zhong et al, 2021). Rescue of dendrite morphology by postnatal rapamycin treatment was reported in the Pi3k E545 and Rheb S16H variants, and rapamycin likely has the same effect for the other variants (Zhang et al, 2019;Zhong et al, 2021).…”
Section: Conserved Mtorc1-dependent Phenotypes Across Pi3k-mtor and Gator1 Gene Variantsmentioning
confidence: 99%
“…We used anti-Ki67 (clone MM1, RTU Leica Microsystem) and rabbit anti PS6 (1:100, clone 4857, Cell Signaling Technology, Danvers). Finally, we also used rabbit anti FLNA (1:250 clone EP2405Y; Abcam ab76289), as a recent study reported that filamin A antibodies stained Giant/Balloon cells and dysmorphic neurons in samples from TSC and FCD patients (Zhang et al, 2020). Primary antibody binding to tissue sections was visualized using BOND Polymer Refine Detection (Leica Microsystem) except for parvalbumin (1:100 secondary horseradish peroxidase-conjugated IgG antisheep, Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical observation, genetic analysis, and laboratory research have assisted in developing a robust understanding of the neuropathology of TSC. There remain questions as to the extent that hamartin and tuberin regulate mTORC1-independent pathways that contribute to TSC pathology (Zhang et al, 2014 , 2020 ). However, the importance of the mTOR pathway is underscored by the clinical utility of rapamycin-like compounds that inhibit mTORC1 (Franz and Capal, 2017 ).…”
Section: The Molecular Genetics Of Tscmentioning
confidence: 99%